Palladium‐ and Ruthenium‐Catalyzed Cycloisomerization of Enynamides and Enynhydrazides: A Rapid Approach to Diverse Azacyclic Frameworks1. Issue 35 (15th July 2013) - Walker, P. Ross; Campbell, Craig D.; Suleman, Abid; Carr, Greg; Anderson, Edward A.
<x xml:space="preserve">Abstract</x> I want to ride my azacycle: The title reaction of enynamides affords a wide diversity of azacycles. The reactions are high‐yielding, highly stereoselective, and proceed rapidly under mild reaction conditions. Equivalent transformations using enynhydrazides offer new routes to pyrazole and indazole scaffolds. Boc=tert‐butoxycarbonyl, EWG=electron‐withdrawing group, Ns=4‐nitrobenzenesulfonyl, Ts=4‐toluenesulfonyl.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>